Effect of 5 Genetic Variants Associated with Lung Function on the Risk of COPD, and their Joint Effects on Lung Function. - Soler Artigas, M; Wain, L; Repapi, E; Obeidat, M; Sayers, I; Burton, P; Johnson, T; Zhao, J; Albrecht, E; Dominiczak, A; Kerr, S; Smith, B; et al. (2011)
RATIONALE: Genomic loci are associated with forced expiratory volume in one second (FEV1) or the ratio of FEV1 to forced vital capacity (FVC) in population samples, but their association with COPD has not yet been proven, nor have their combined effects on lung function and COPD been studied. OBJECTIVES: To test association with COPD of variants at five loci (TNS1, GSTCD, HTR4, AGER and THSD4) and evaluate joint effects on lung function and COPD of these SNPs, and variants at the previously reported locus near HHIP. METHODS: Sampling from 12 population-based studies (n=31,422), we obtained genotype data on 3,284 COPD cases and 17,538 controls for sentinel SNPs in TNS1, GSTCD, HTR4, AGER and THSD4. In 24,648 individuals (including 2,890 COPD cases and 13,862 controls), we additionally obtained genotypes for rs12504628 near HHIP. Each allele associated with lung function decline at these six SNPs contributed to a risk score. We studied the association of the risk score to lung function and COPD. RESULTS: Association with COPD was significant for three loci (TNS1, GSTCD, HTR4) and the previously reported HHIP locus, and suggestive and directionally consistent for AGER and TSHD4. Compared with the baseline group (7 risk alleles), carrying 10-12 risk alleles was associated with a reduction in FEV1 (β=-72.21 ml, P=3.90x10-4) and FEV1/FVC (β=-1.53%, P=6.35x10-6), and with COPD (OR=1.63, P=1.46x10-5). CONCLUSIONS: Variants in TNS1, GSTCD and HTR4 are associated with COPD. Our highest risk score category was associated with 1.6-fold higher COPD risk than the population average score.